1983
DOI: 10.1002/ajmg.1320150409
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of neural tube defects among first‐, second‐, and third‐degree relatives of probands: Results of a United States study

Abstract: Data on the occurrence of neural tube defects in first-, second-, and third-degree relatives of probands were collected in a United States study. The proportions of affected individuals were 3.2%, 0.5%, and 0.17% respectively. These findings are compared to those from other recent North American studies, and differences are discussed. It is pointed out that accurate recurrence risk figures may not be available, and that caution should be used when counseling families with relatives who are affected with NTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…18 In our study we also had higher rate of previous history of NTDs in NTD group and it was observed that 93.3% of the women were having a baby with NTDs in this group whereas in the controlled group 94.4% were having previous normal babies. which favored the hypothesis that prevention of the first occurrence of NTDs is of real public health importance.…”
supporting
confidence: 60%
“…18 In our study we also had higher rate of previous history of NTDs in NTD group and it was observed that 93.3% of the women were having a baby with NTDs in this group whereas in the controlled group 94.4% were having previous normal babies. which favored the hypothesis that prevention of the first occurrence of NTDs is of real public health importance.…”
supporting
confidence: 60%
“…Other genetic mechanisms of transmission, such as an X-linked recessive gene, a dominant gene with variable penetrance or polygenic transmission have been suggested to explain this tendency to recur within families. 5 In our study none of the parents gave history of a previously affected child and hence genetic co relation was not assessed in our study.…”
Section: Discussionmentioning
confidence: 94%
“…However, we also found that the proposal of the multifactorial threshold hypothesis for common human birth defects was in fact partly based on data for NTDs (Carter, 1969, 1974). Furthermore, subsequent extensive studies of human NTDs (Lippman‐Hand et al, 1978; Toriello and Higgins, 1983; Czeizel and Metneki, 1984; Hunter, 1984; Koch and Fuhrmann, 1985) tested the multifactorial model's predictions and tested and rejected the hypotheses of simple recessive or dominant inheritance with low penetrance, at least for Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%